2023
DOI: 10.1155/2023/2345835
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Automatic Spine Segmentation Using Patch-Based Deep Learning

Abstract: CT vertebral segmentation plays an essential role in various clinical applications, such as computer-assisted surgical interventions, assessment of spinal abnormalities, and vertebral compression fractures. Automatic CT vertebral segmentation is challenging due to the overlapping shadows of thoracoabdominal structures such as the lungs, bony structures such as the ribs, and other issues such as ambiguous object borders, complicated spine architecture, patient variability, and fluctuations in image contrast. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…SC is computed based on AoD and SoE. The other indicators such as recall, precision, specificity, F1-score, and accuracy [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ] are computed in Equations (1)–(5) below: where TP, TN, FN, and FP represent true positive, true negative, false negative, and false positive.…”
Section: Performance Indicatormentioning
confidence: 99%
“…SC is computed based on AoD and SoE. The other indicators such as recall, precision, specificity, F1-score, and accuracy [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ] are computed in Equations (1)–(5) below: where TP, TN, FN, and FP represent true positive, true negative, false negative, and false positive.…”
Section: Performance Indicatormentioning
confidence: 99%
“…Besides, recent advances in medical diagnosis have witnessed a surge in the adoption of deep learning methods. Studies such as (Ahmad, Ai, et al, 2019; Ahmad, Ding, et al, 2019; Alzghoul et al, 2023; Bataineh, 2019; Doppala et al, 2023; Furqan Qadri et al, 2019; Habib & Qureshi, 2023; Hirra et al, 2021; Qadri et al, 2019; Qadri et al, 2021; Qadri et al, 2022; Qadri et al, 2023; Vamsi et al, 2022) have demonstrated deep learning ability in dealing with large datasets and complex patterns. While deep learning methods provide robust performance (Ahmadian et al, 2021; Arora et al, 2022; Jalali, Ahmadian, Ahmadian, et al, 2022; Jalali, Arora, Panigrahi, et al, 2022; Jalali, Osorio, Ahmadian, et al, 2022; Mehnatkesh et al, 2023; Saffari et al, 2023), their computational density and the need for extensive data and training can be limited in certain scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The success of deep learning is always attributed to the growing number of large data sets and powerful computing hardware, especially in the field of medical images, which rely heavily on accurate labels and gold standards [8,9]. However, the scarcity of medical image data annotation, small sample size, uneven distribution, and poor domain generalization still seriously affect the development of related fields.…”
Section: Introductionmentioning
confidence: 99%